Surgical Management of Vestibular Schwannoma: Practice Pattern Analysis via NSQIP. (March 2020) - Patel, Vijay A.; Dunklebarger, Mitchell; Banerjee, Kalins; Shokri, Tom; Zhan, Xiang; Isildak, Huseyin
Objective: Characterize current perspectives in the surgical management of vestibular schwannoma (VS) to guide otolaryngologists in understanding United States practice patterns. Methods: A retrospective analysis of ACS-NSQIP database was performed to abstract all patients from 2008 to 2016 who underwent VS resection using ICD-9/10 codes 225.1 and D33.3, respectively. The specific surgical approach employed was identified via CPT codes 61520, 61526/61596, and 61591, which represent retrosigmoid (RS), translabyrinthine (TL) and middle cranial fossa (MCF) approaches, respectively. Analyzed outcomes include general surgical complications, total length of stay, and reoperation. Results: A total of 1671 VS cases were identified, 1266 (75.7%) were RS, 292 (17.5%) were TL, and 114 (6.8%) were MCF. The annual number of cases increased over the study period from 15 to 375, which is chiefly attributed to increased institutional participation in ACS-NSQIP. Perioperative variables including BMI ( P < .001), ASA class ( P = .004), ethnicity ( P = .008), operative time ( P < .001), and reoperation ( P < .001) were found to be statistically significant between cohorts. Increased utilization of RS approach was consistent over the entire study period, with significantly more RS performed than either TL or MCF. Finally, a statistically significant difference with respect to general surgical complication rates was not noted between surgical approaches. Conclusions: There is increased employment of RS approach for the operative management of VS, which likely is the result of increased reliance on both stereotactic radiosurgery and observation as alternative treatment strategies.